PLAQUE ASSAY PROCEDURE FOR COLORADO TICK FEVER VIRUS - Deig, E. Frank (1964)
Deig, E. Frank (University of California, Berkeley), and H. M. S. Watkins. Plaque assay procedure for Colorado tick fever virus. J. Bacteriol. 88:42–47. 1964.—A reproducible plaque assay procedure is described for the quantitation of Colorado tick fever virus in a cell line established from embryonic hamster tissue. Under the best conditions, plaques approximately 4 mm in diameter were formed after incubation at 37 C of 4 to 6 days. Several environmental variables in the procedure were studied. Efficiency was increased markedly by combining the virus during adsorption with serum proteins, and by carrying out this step at 25 C rather than at 37 C. The overlay medium used contained metabolites which promoted cell viability for periods greater than 1 week, and allowed plaques to develop. Plaque formation was relatively insensitive to a variation in pH between 7.1 and 8.1 (with optimal concentrations of bicarbonate). However, plaque development was inhibited with medium containing greater than 0.22% bicarbonate (at optimal pH), or when the initial pH was less than 7.0.